1991
DOI: 10.1111/j.1365-2125.1991.tb03916.x
|View full text |Cite
|
Sign up to set email alerts
|

The interactions between nisoldipine and two beta‐adrenoceptor antagonists‐atenolol and propranolol.

Abstract: 1. The interactions between the dihydropyridine calcium antagonist nisoldipine and two beta‐adrenoceptor blocker drugs (atenolol and propranolol) were investigated in two groups of healthy normotensive subjects. 2. The steady state plasma concentrations of both beta‐ adrenoceptor blockers were significantly altered by the addition of nisoldipine: for propranolol there were significant increases in Cmax, by about 50%, and in AUC by about 30% and for atenolol there was a significant increase in Cmax, by about 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It has been reported that there is a little pharmacokinetic interaction between -blocking agents and dihydropyridine Ca-channel blockers (Smith et al 1987;Elliot et al 1991). In this experiment, the results showed that the plasma carvedilol concentrations and AUC 0 !…”
Section: Discussionmentioning
confidence: 57%
“…It has been reported that there is a little pharmacokinetic interaction between -blocking agents and dihydropyridine Ca-channel blockers (Smith et al 1987;Elliot et al 1991). In this experiment, the results showed that the plasma carvedilol concentrations and AUC 0 !…”
Section: Discussionmentioning
confidence: 57%
“…Pharmacokinetic changes were seen with the combinations of atenolol and nitrendipine, [31] and atenolol with nisoldipinePO] Pharmacokinetic changes were more marked with a combination of propranolol and nisoldipine than atenolol and nisoldipine. [30] Coadministration of oral verapamil with oral atenolol [33] resulted in a variable increase in atenolol steady-state plasma concentrations in a group of patients receiving long term maintenance therapy with these 2 agents. The observed prolongation of the PR interval, however, is likely to contribute to intolerance of the combination of atenolol and verapamil in individuals.…”
Section: 1 Afenololmentioning
confidence: 99%